2022
DOI: 10.3390/fermentation8120672
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics as a Friendly Antibiotic Alternative: Assessment of Their Effects on the Health and Productive Performance of Poultry

Abstract: Antibiotics have been used to maintain the overall health of poultry by increasing production efficiency, promoting growth, and improving intestinal function for more than 50 years. However, they have a number of side effects, such as antibiotic resistance, gut dysbiosis, destruction of beneficial bacteria, and the potential to spread diseases to humans. In order to address the aforementioned issues, a lot of effort is put into the development of antibiotic alternatives. One of them is the use of probiotics th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 116 publications
1
10
0
Order By: Relevance
“…Dietary addition of SCFP in the experimental birds did not alter the concentration of glucose, total protein, albumin, triglyceride and uric acid in serum, which confirmed the absence of adverse side effects in the studied birds [ 35 ]. In agreement with earlier reports [ 43 , 44 ], the present study also confirmed significant reduction of blood cholesterol concentration in SCFP-treated birds compared to the control or probiotic-fed groups. Lower serum concentration of cholesterol in the birds is associated with production of eggs with a low cholesterol level, which is especially popular among health-conscious consumers [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Dietary addition of SCFP in the experimental birds did not alter the concentration of glucose, total protein, albumin, triglyceride and uric acid in serum, which confirmed the absence of adverse side effects in the studied birds [ 35 ]. In agreement with earlier reports [ 43 , 44 ], the present study also confirmed significant reduction of blood cholesterol concentration in SCFP-treated birds compared to the control or probiotic-fed groups. Lower serum concentration of cholesterol in the birds is associated with production of eggs with a low cholesterol level, which is especially popular among health-conscious consumers [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Modern industrial poultry farming, both urgent and broiler, is widely used all over the world by many approaches or alternative natural feed additives in feed to increase productivity, improve animal welfare and, ultimately, achieve the sustainability of animal husbandry [ 2 , 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 33 ]. Of course, the ban on the use of antibiotics when feeding poultry and other types of productive farm animals has positively affected the increase in alternative sources of biologically active substances, such as pro- and prebiotics [ 10 , 11 , 22 , 27 ], enzymes [ 11 , 34 ], symbiotics [ 27 , 34 ], organic acids [ 35 , 36 , 37 , 38 , 39 ], essential oils [ 10 , 11 , 13 , 20 ], medicinal herbs [ 36 , 40 , 41 ], phytobiotics [ 7 , 8 , 9 , 11 , …”
Section: Discussionmentioning
confidence: 99%
“…Currently, manufacturers of feed additives face two tasks: the production of additives with a bactericidal effect, as well as stimulating the growth and development of high-quality muscle tissue [ 20 , 21 , 22 , 23 ]. There are more than a dozen solutions on the market having the above properties with varying degrees of effectiveness, such as probiotics [ 19 , 22 , 24 ], prebiotics [ 24 , 25 , 26 ], symbiotics [ 25 , 26 , 27 ], enzymes [ 25 , 26 ], phytobiotics [ 2 , 3 , 13 , 20 , 21 ] and plant extracts [ 8 , 9 , 14 , 23 ]. Consequently, the aim of our study was to assess complex phytobiotic feed additives (CPFA) and their combined effect on the productivity, meat performance and blood picture of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…However, coccidiosis in chickens can be prevented over time by rotation strategies that use both medicines and vaccines in succeeding flocks [ 56 ]. As genetic technology progresses, vaccines containing genes encoding immunomodulatory polypeptides will be developed [ 57 ].…”
Section: Methods Used To Control Avian Coccidiosismentioning
confidence: 99%